PENYULUHAN DAN PEMBERDAYAAN MASYARAKAT DALAM PENANGANAN STUNTING DI DESA JATISARI BANDUNG - Marlina, Lusi; Monica, Rizqy Dimas; Yurika, Yurika; Damayanti , Eva; Pujilestaria , Intan (ASOSIASI IDEBAHASA KEPRI, 2025)
This network service (PkM) initiative become designed to address stunting in Jatisari Village through training, education, and community empowerment. the program targeted upgrades in dietary understanding, abilities for getting ready balanced complementary foods (MP-ASI), and hygiene practices. The intervention caused a great boom in community know-how approximately stunting (from 55% to 85%), complete mastery in MP-ASI guidance (100%), and proper handwashing practices (90%) among participants. strong enthusiasm and lively participation (80%–90%) additionally endorsed the status quo of nearby projects together with the “mothers for vitamins cognizance” (Ibu Peduli Gizi/IPG) organization. basic, the program made a significant contribution to elevating recognition and equipping the network with practical capabilities for stunting prevention, mainly for the duration of the vital first 1,000 days of existence, highlighting its capability for lengthy-time period sustainability.